Fostering Interest in Sharia Insurance Agent Certification: A Multidimensional Dialogue between Cultural Dynamics and Social Realities - Faridah, Nurhayani; Gafur, Abdul; Badrian; Jahra, Pati Matu; Syarqawie, Fithriana (Pascasarjana UIN ANTASARI Banjarmasin, 2024)
This study examines the influence of motivation and perception on the interest of Sharia Insurance department students at UIN Antasari Banjarmasin in obtaining Sharia insurance agent certification. A multidimensional approach integrating cultural dynamics and social realities is adopted to understand the complexity of this phenomenon. Quantitative methods with regression analysis are used to analyze data from 120 respondents. The research findings indicate that motivation and perception have a significant influence both individually and simultaneously on students' interest in pursuing Sharia insurance agent certification. Cultural dynamics, such as Islamic values and local traditions, influence students' motivation and perception towards Sharia insurance agent certification. Social realities, such as economic conditions and job opportunities, affect students' interest in undergoing certification processes. This study emphasizes the importance of building positive motivation and perception among Sharia Insurance students to enhance their interest in obtaining Sharia insurance agent certification. These efforts need to consider the cultural dynamics and social realities faced by students.